Roasted Coffee Extracts as Corrosion Inhibitors for Mild Steel in HCL Solution - Souza,Elaine Cesar do Carmo Assumpção de (2016)
The behavior of roasted coffee extract and its isolated high molecular weight fraction have been investigated as carbon steel corrosion inhibitors in HCl solution by weight loss measurements, potentiodynamic polarization curves, electrochemical impedance and scanning electron microscopy analysis. All results showed that the high molecular weight fraction, rich in melanoidins, present an important role in the inhibitory action of the roasted coffee extract in the acid corrosion of carbon steel.